Effect of delayed light-curing on solubility, color stability, and opacity of Fuji II LC glass ionomer cement: original article - Nejatifard, Marzieh; Panahandeh, Narges; Ghasemi, Amir; Torabzadeh, Hassan (Brazilian Dental Science, 2022)
Objective: Resin-modified glass ionomer (RMGI) cements are among the commonly used restorative materials in low stress-bearing areas and also for temporary restorations. The competition between acid-base reactions and light polymerization reactions in delayed curing of RMGIs can affect their physical and mechanical properties, as well as their degree of conversion. Since solubility, color stability, and opacity are among the main physical properties affecting the durability and clinical service of RMGI restorations, this study aimed to assess the effect of delayed curing on solubility, color stability, and opacity of Fuji II LC RMGI. Material and Methods: This in vitro, experimental study evaluated 80 Fuji II LC RMGI specimens (10 specimens per each in 4 groups) in terms of solubility, color stability, and opacity at 6 months later. Specimens were cured immediately or were cured with 1, 5 and 10 min delay. Results: Maximum solubility and minimum change in opacity and color stability at 6 months were noted in the group with delayed curing by 10 min. A significant difference was noted in the solubility of specimens cured after 10 min and 1 min. Significant differences were also noted in the opacity and color stability of specimens cured after 10 min and all other groups (P < 0.05). Conclusion: Delayed curing by 1 min decreased the solubility of RMGI specimens compared with immediate curing or curing after 5 min. Although this difference did not reach statistical significance. Color stability and changes in opacity are mainly influenced by the acid-base reactions rather than polymerization reactions. KEYWORDS Glass Ionomer cement; Fuji II LC cement; Solubility; Color; Opacity.